Developing Vocabulary Mastery of the Eighth Grade Students of MTs Negeri 2 Palu through English Comic Strips - Zulvin, Moh.; Rofiqoh, Rofiqoh; Maf'ulah, Maf'ulah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The objective of this research is to prove whether the use of English comic strips can develop vocabulary mastery of the eighth grade students of MTs Negeri 2 Palu. This research used a quasi-experimental research design which involved two groups experimental and control groups. The sample was class VIII B as the experimental group and class VIII A as the control group. In collecting the data, the instrument used an exercise for each meeting. Both experimental and control group given pre-test and post-test. The experimental was given treatment while the control treated by regular teaching. The result showed that the students’ mean score of the experimental group was 66.03 on the pre-test and 82.97 on the post-test. Furthermore, the students’ mean score of the control group was 64.26 on the pre-test and 75.5 on the post-test. Consulting to the t-table value by applying degree of freedom (df) and 0.05 level of significance, the researcher found that the value of the t-counted (2.02) is higher than the t-table (1.651). It means that the hypothesis is accepted. In other words, the use of English Comic Strips can develop vocabulary mastery of the eighth grade students of MTs Negeri 2 Palu. The implication of applying comic strip in teaching vocabulary is that comic strip is able to attract students’ attention and help students enhance vocabulary.